2008
DOI: 10.1083/jcb.200804062
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-10 and actin filaments are essential for mitotic spindle function

Abstract: Abbreviations used in this paper: HMM, heavy meromyosin; LatB, latrunculin B; MO, morpholino; Myo10, myosin-10.The online version of this paper contains supplemental material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
283
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(312 citation statements)
references
References 44 publications
20
283
1
1
Order By: Relevance
“…They convert the chemical energy derived from ATP hydrolysis into directed motion along actin and are responsible for a wide variety of intracellular motilities and for muscle contraction. Mammalian myosin-10 was originally found to localize to the tips of filopodia (3,4) and is known to be important for filopodial formation and extension (4-6), phagocytosis (7), cell migration (8), and mitotic spindle length maintenance and anchoring (9). It is an ∼240-kDa protein consisting of an N-terminal, consensus motor region (which binds actin, hydrolyses ATP, and produces force and movement), a light chain binding domain (LCBD) with three IQ motifs (10), and a stable single alpha-helix (SAH) followed by a tail region containing, an antiparallel coiled-coil (APCC) region, a proline, glutamate, serine, and threonine rich (PEST) domain, three pleckstrin homology (PH) domains, a myosin tail homology 4 (MyTH4) domain, and a band 4.1, ezrin, radixin, moesin (FERM) domain (Fig.…”
mentioning
confidence: 99%
“…They convert the chemical energy derived from ATP hydrolysis into directed motion along actin and are responsible for a wide variety of intracellular motilities and for muscle contraction. Mammalian myosin-10 was originally found to localize to the tips of filopodia (3,4) and is known to be important for filopodial formation and extension (4-6), phagocytosis (7), cell migration (8), and mitotic spindle length maintenance and anchoring (9). It is an ∼240-kDa protein consisting of an N-terminal, consensus motor region (which binds actin, hydrolyses ATP, and produces force and movement), a light chain binding domain (LCBD) with three IQ motifs (10), and a stable single alpha-helix (SAH) followed by a tail region containing, an antiparallel coiled-coil (APCC) region, a proline, glutamate, serine, and threonine rich (PEST) domain, three pleckstrin homology (PH) domains, a myosin tail homology 4 (MyTH4) domain, and a band 4.1, ezrin, radixin, moesin (FERM) domain (Fig.…”
mentioning
confidence: 99%
“…Myosin X is found at the mitotic and meiotic spindle, where it sets the orientation of the spindle relative to the substrate and influences spindle length (3,4). However, myosin X is more commonly found in interphase cells at the tips of filopodia (5).…”
mentioning
confidence: 99%
“…Given that Myo10 interacts with TPX2 22 and ADD1 42, this prompted us to examine whether TPX2 interacts with ADD1 through Myo10. Indeed, we found that TPX2 interacted with ADD1 in mitosis, but the interaction was not detected in interphase (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Myo10 is the ADD1 binding partner on mitotic spindles 42 and its role in spindle positioning and spindle length control is F‐actin‐dependent 22. In fact, the spindle F‐actin has been shown to surround mitotic spindles during early Xenopus embryo mitosis 22. Arp2/3 protein complex, which is involved in the nucleation and assembly of branched actin filaments, has been shown to participate in the formation of the spindle F‐actin 52, 53.…”
Section: Discussionmentioning
confidence: 99%